In Vitro The Effect of Canals Instrumented With Three Rotary Ni-Ti Systems on The Dislocation Resistance of Guttafusion® Versus Single Cone Obturation Technique - Ameen, Rafal S; AlHashimi, Raghad A (Journal of Baghdad College of Dentistry, 2017)
Background: Complete seal of the root canal system following its chemo-mechanical debridement plays a pivotal role for achieving successful endodontic treatment. This can be established by reducing the gaps between the core filling material and root canal wall. Aim: To assess and compare the dislocation resistance of root canals obturated with GuttaFusion® and TotalFill BC sealer versus single cone obturation technique and TotalFill BC sealer after instrumentation of the canals with WaveOne, ProTaper Next and ProTaper Universal system. Material and Method: Sixty extracted human permanent mandibular premolars were conducted in the current study. The teeth were decorated and left the root with 15mm length; the roots were divided randomly into three main groups, twenty roots in each group. The roots were instrumented with different rotary systems using crown down technique according to the groups: (Group I) was instrumented with WaveOne files. (Group II) was instrumented with ProTaper Next system and (Group III) was instrumented with ProTaper Universal system. For each group the same irrigation regimen was used, 3 mL of 5.25% sodium hypochlorite and 3 mL of 17% EDTA to remove the smear layer. Then, Group I was also subdivided randomly into two subgroups of ten samples each, (Group I A) obturated with single cone gutta-percha and (Group I B) filled with GuttaFusion®. Group II was divided into (Group II A) obturated with single cone gutta-percha and (Group II B) filled with GuttaFusion®. Group III was divided into (Group III A) obturated with single cone gutta-percha and (Group III B) obturated with GuttaFusion®. In the present study, TotalFill BC sealer was used for all the tested groups. Then, the roots were embedded in clear acrylic resin and each root sectioned into three sections of 2mm thick (apical, middle and coronal). The push-out bond strength values represented by (MPa) unit was calculated by dividing the load on the surface area and the last was measured in collaboration with AutoCAD system software program. Failure mode analysis was carried out to examine the type of failure in each sample by using a stereomicroscope. Results: The results showed highly significant differences among the main groups that instrumented with different rotary systems (WaveOne, ProTaper Next and ProTaper Universal system). There were highly significant differences between the two obturation techniques of the subgroups (single cone gutta-percha versus GuttaFusion®). However; Gutta-Fusion® showed highest bond strength value than single cone obturation technique. The coronal third slices of all groups showed highest value of bond strength in comparison to the middle thirds and apical thirds. In the meantime, the middle third slices showed bond strength higher than that of the apical thirds for all groups. Statistical analysis was performed by using two way ANOVA and LSD tests. Conclusions: The instrumentation techniques and the obturation materials significantly affected the push-out bond strength values of obturation system. The highest value was appointed in root canals instrumented with ProTaper Universal System; obturated with GuttaFusion® and BC sealer, whereas, the lowest bond strength was appeared at canals instrumented with ProTaper Next; obturated with single cone gutta-percha and BC sealer.